Public Perception of the Performance of SAMSAT Jambi City: SEM-PLS Analysis on the Quality of Motor Vehicle Tax Services Based on SERVQUAL - Aditia, M. Reyhan; Sutan, Arrisy Jorgi; Beriansyah, Alva; Hapsa (Journal of Public Administration and Government, 2025)
Public services are a real reflection of the quality of governance which plays a role as the main indicator of the country's success in fulfilling the basic rights of its citizens. In the context of regional autonomy, improving the quality of public services is a strategic aspect to strengthen the legitimacy of the government and build public trust in public institutions . This study aims to analyze public perception of the quality of Motor Vehicle Tax payment services at SAMSAT Jambi City using the SERVQUAL model which includes five main dimensions, namely tangibles, reliability, responsiveness, assurance and empathy. The research method uses a quantitative approach with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) analysis technique based on questionnaire data from taxpayers who have paid motor vehicle taxes. The results of the study show that all dimensions of SERVQUAL are proven to be valid and reliable and have a positive and significant influence on the quality of public services. These findings confirm that the reliability, responsiveness, assurance, and empathy of officers are the dominant factors that shape the public's positive perception of the performance of motor vehicle tax payment services at SAMSAT Jambi City. Empirically, this study concludes that improving the quality of public services needs to be directed at strengthening the professionalism of servant workers, developing empathy and interpersonal communication, and optimizing service facilities that support the creation of responsive, effective, and community satisfied public services.